2023
DOI: 10.1017/gmb.2023.9
|View full text |Cite
|
Sign up to set email alerts
|

Regular consumption of lacto-fermented vegetables has greater effects on the gut metabolome compared with the microbiome

Abstract: The industrialisation of Western food systems has reduced the regular consumption of lacto-fermented vegetables (LFV). Consuming LFV may exert health benefits through the alteration of the gut microbiome, but the mechanisms involved remain unclear. To start understanding the possible benefits of LFV, we compared faecal microbial diversity and composition, as well as dietary habits between individuals who regularly consume LFV (n = 23) and those who do not (n = 24). We utilised microbial DNA amplicon sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…By contrast, participants consumed 2 servings of kombucha for four weeks, suggesting that in our short intervention study, this fermented food threshold or magnitude may have been insufficient to induce broad microbial remodeling as observed previously (Wastyk et al, 2021). Nevertheless, our findings are in line with other studies that have reported no changes to microbiota diversity as a result of fermented food intake in comparison with controls or pre-intervention state (Alvarez et al, 2020; Berding et al, 2022; Guse et al, 2023; Taylor et al, 2020; Walsh et al, 2023). For instance, a randomized, double- blind, controlled intervention study evaluated the effect of daily consumption of two doses of a multi-strain fermented milk product for 4 weeks on the gut microbiome.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…By contrast, participants consumed 2 servings of kombucha for four weeks, suggesting that in our short intervention study, this fermented food threshold or magnitude may have been insufficient to induce broad microbial remodeling as observed previously (Wastyk et al, 2021). Nevertheless, our findings are in line with other studies that have reported no changes to microbiota diversity as a result of fermented food intake in comparison with controls or pre-intervention state (Alvarez et al, 2020; Berding et al, 2022; Guse et al, 2023; Taylor et al, 2020; Walsh et al, 2023). For instance, a randomized, double- blind, controlled intervention study evaluated the effect of daily consumption of two doses of a multi-strain fermented milk product for 4 weeks on the gut microbiome.…”
Section: Discussionsupporting
confidence: 93%
“…While overall shifts in microbial diversity were unaffected, our study observed that the composition of the gut microbiome was impacted by kombucha supplementation. We detected significantly altered differential abundance of selected taxa between consumers and controls at the end of intervention, a pattern consistent with earlier studies (Galena et al, 2022; Guse et al, 2023; Taylor et al, 2020; Walsh et al, 2023; Wastyk et al, 2021). Specifically, we observed the enrichment of 36 species and the concurrent depletion of 14 taxa associated with kombucha consumers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation